Multiple supernumerary teeth in a non-syndromic patient: A case report - Khlood Alkurdi; Abdullah Alshammari; Khalid Alkurdi; Abdulmjeed Sadoon; Paul Hammans (Elsevier, 2023)
Supernumerary teeth are stomatological anomalies where teeth exist in excess number to the normal dental count. Our case presents a healthy Saudi Arabian male with five supernumerary teeth and a family/relative history completely clear of such an anomaly. He was diagnosed during his checkup with the general dental practitioner and was referred to the maxillofacial surgeon in Canberra, Australia. His treatment involved surgical removal of four supernumerary teeth under general anesthesia and enforcement of good oral hygiene.